Insight Into the Ultrastructure of Antennal Sensilla of Mythimna separata (Lepidoptera: Noctuidae). Issue 1 (10th September 2015) - Chang, Xiang-Qian; Zhang, Shu; Lv, Liang; Wang, Man-Qun
Abstract : The oriental armyworm, Mythimna separata (Walk), is one of the most serious pests of cereals in Asia and Australasia. The structure and distribution of the antennal sensilla of M. separata were studied by scanning electron microscopy and transmission electron microscopy. The results showed that antennae of both female and male M. separata are filiform in shape. Three groups and seven morphological sensillum types were recorded in both sexes, including uniporous sensilla (sensilla chaetica), multiporous sensilla (sensilla trichodea, basiconica, coeloconica, and styloconica), and aporous sensilla (sensilla squamiformia and Böhm bristles). S. trichodea, which were the most abundant sensilla, was made of three subtypes (ST I, ST II, and ST III) according to external features and two subtypes of s. basiconica (SB I and SB II) and s. coeloconica (SCo I and SCo II) were identified, respectively. Sexual dimorphisms in sensilla of M. separata were mainly perceived as the variations in the numbers of several sensilla subtypes. Also, the possible functions of the antennal sensilla were discussed. These results contribute to our understanding of the function of antennae in the behavior of M. separata .